Customer-based Brand Equity for a Tourism Destination (CBBETD): the Specific Case of Bandung City, Indonesia - Yuwo, Hartanto; Ford, John B.; Purwanegara, Mustika Sufiati (Organizations and Markets in Emerging Economies, 2019)
This study examines in detail the use of customer-based brand equity for a tourism destination (CBBETD) as a strategic tool for use with a specific city (Bandung City, Indonesia in this instance). The CBBETD scale developed by Konecnik (2005) and empiricized by Konecnik and Gartner (2007) was successfully adapted using qualitative and quantitative refinements for the city of Bandung. A sample of 400 visitors to Bandung was surveyed, and empirical psychometric assessment was run. The scale required minor adaptations but was found to be appropriate for use in this new context. The components of customer-based brand equity for a tourism destination were found to be: awareness, image, quality and loyalty. The successful adaptation of the scale is encouraging as it provides strategic insight on strengthening destination positioning in the minds of both current and future tourists. Managerial implications and suggestions for future research are provided.
Keywords: tourism marketing; city branding; brand equity